Towards the Recognition of Municipal Development with an Environmental Sustainability Approach Case of San Vicente de Chucurí (Revista cientifica In Vestigium Ire, 2019)
The article recapitulates the research that seeks to respond to difficulties in the disclosure of data on "sustainable development " outlined in the municipal development plans in Colombia, taking into account that traditional accounting shows only financial sustainability, preventing the affirmation of environmental and social sustainability, fully including on the economic , requiring the appropriation of reports that make feasible the integral evaluation of sustainability. The research focused on sustainability with priority on the environmental issue, adopting San Vicente de Chucurí (Santander, Colombia) as study municipality, in whose development plan it assumes environmental preservation and management, as well as agro - industrialization, but The recognition of environmental sustainability has been difficult with the current accounting tool and the indicators proposed by the UN. When approaching this municipality, it was evident that the purpose of sustainability and social welfare was raised but does not have indicators and revelations that show this as a reality.Reason why indicators are suggested to calculate them and based on the results, know the reality of the municipality against sustainable development.
Keywords: Indicators of Sustainability; Territorial Development Plan; Environmental Accounting; Agricultural Sector